2014
DOI: 10.1111/jpc.12761
|View full text |Cite
|
Sign up to set email alerts
|

Oral health and risk factors for dental disease of Australian young people in custody

Abstract: Young people entering custody have poor oral health, with those from geographically remote areas without water fluoridation at highest risk. The incarceration period is an opportunity for oral health improvements in these young people through access to dental treatment services. Better triaging systems are needed to identify those of greatest priority, and prevention services are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…2,4 The confluence of each determinant provides a nexus for intractable social disadvantage and exclusion, and all increase risk for anhedonia and offending behaviours. 25,26 An additional and important factor contributing to over-representation of Aboriginal and Torres Strait Islanders in detention in Australia is the effect of intergenerational harms seeded at colonisation. [27][28][29][30] Incarceration and detention of any child or adolescent is a significant adverse determinant and traumatic to the individual and their family.…”
Section: Introductionmentioning
confidence: 99%
“…2,4 The confluence of each determinant provides a nexus for intractable social disadvantage and exclusion, and all increase risk for anhedonia and offending behaviours. 25,26 An additional and important factor contributing to over-representation of Aboriginal and Torres Strait Islanders in detention in Australia is the effect of intergenerational harms seeded at colonisation. [27][28][29][30] Incarceration and detention of any child or adolescent is a significant adverse determinant and traumatic to the individual and their family.…”
Section: Introductionmentioning
confidence: 99%
“…The few available studies, which assessed the oral health among these individuals, showed a high prevalence of dental caries and periodontal diseases. 23 Moreover, in these adolescents a very poor oral health-related quality of life was detected, which is associated with untreated dental caries and discomfort in the teeth or mouth. 21 In addition to poor oral health and oral hygiene, halitosis is also associated with hyposalivation.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this important knowledge, to the best of the authors' knowledge, no study has investigated the self‐perception of halitosis among this group of adolescents. The few available studies, which assessed the oral health among these individuals, showed a high prevalence of dental caries and periodontal diseases 23 . Moreover, in these adolescents a very poor oral health‐related quality of life was detected, which is associated with untreated dental caries and discomfort in the teeth or mouth 21…”
Section: Discussionmentioning
confidence: 99%
“…51 Both reviews presented their findings as narrative summaries rather than meta-analyses due to the heterogeneous nature of the included studies. 50,51 The primary studies which included adult participants identified by the NHMRC review assessed caries 57,58 and tooth loss. [59][60][61][62] Additional adult studies included in the Canadian review assessed caries severity (DMFT/S), [63][64][65][66] caries prevalence, 67 tooth loss 68,69 and dental service use.…”
Section: Systematic Reviewsmentioning
confidence: 99%